A decade of intelligent packaging for meat with insight from smart packaging literature: Trends, innovations, and future prospects - a systematic review and network analysis - Hidayat, Serli Hatul; Novrain, Abel Yandi; Irwan, Irwan (Hasanuddin University Food Science and Technology Study Program, 2025)
Packaging no longer serves merely as a protector or wrapper for products, but also functions to maintain quality, safety, and extendthe shelf life of food products. Especially for meat products, the demand for packaging systems capable of monitoring quality inreal-time continues to grow. This is because meat products are susceptible to damage due to contamination and microbialoxidation. Therefore, intelligent packaging offers a solution by integrating sensor and indicator technologies to detect changes inthe environment such as pH, temperature, and volatile compounds. This study aims to examine trends, publications, and researchdevelopments in intelligent packaging for meat packaging from 2014 to 2024 using bibliometric methods. Additionally, a systematicliterature review method was used to examine the application of various types of intelligent packaging on meat. Data was collectedfrom the Scopus database, which covers various applications of intelligent packaging on meat products. The application ofintelligent packaging shows an increasing trend each year. The most commonly applied technologies include pH indicators, gas sensors,temperature-time indicators, and RFID. These technologies can be used to monitor the freshness, temperature, and quality of meat.These findings underscore that smart packaging is no longer merely a future innovation but a strategic solution ready for adoption bythe food industry to enhance the safety, efficiency, and competitiveness of meat products in the global market.